Issue Notes - , Editor (Historical Papers, 2022)
The following papers were presented to the Canadian Society of Church History in 2012, but were not made available for publication: Ian Hesketh, “‘Vomited from the Jaws of Hell’: The Controversy of Ecce Homo in Mid-Victorian Britain”; Geoff Read, “Echoes of 1905-Secular Conflict in Interwar France, 1919-40”; Amy Von Heyking, “‘It is a privilege to have a Christian Government’: William Aberhart and the Place of Religion in Alberta’s Public Schools”; Lucille Marr, “Church Women, the Home Front, and the Great War”; Gordon Heath, “Whatever Happened to the British Empire? A Canadian Baptist Case Study”; Melissa Davidson, “Enduing the Cause with Righteousness: Canadian Anglican Views of the Great War, 1914-18”; James T. Robertson, “Anglican and Presbyterian Churches and a Loyalist Theology During the War of 1812”; Scott McLaren, “Rekindling the Canadian Fire: Print Culture and the Reconstruction of Upper Canadian Methodism After the War of 1812”; Denis McKim, “Contesting Christian Loyalty: Religion and Meanings of Britishness in Upper Canada”; Robynne Rogers Healey, “Reconciling Approaches to Non-Violence and Apartheid: Pacifist Conflict among Friends in the 1970s and 1980s”; Indre Cuplinskas, “Doing it Rite: Catholic Action and Liturgical Renewal in Quebec”; Christo Aivalis, “In Service of the Lowly Nazarene: The Canadian Labour Press and a Case for Radical Christianity, 1926-39”; Andrew M. Eason, “Missions, Race and Representation: The Salvation Army’s Portrayal of Africa and India in Victorian Britain”; Bruce Douville, “The Via Media and the Evangelical Road: The Attitudes of Anglican Church Newspapers in Canada West Towards American Slavery and Related Issues, 1837-65”; Nathan Dirks, “An Unknown Legacy: Canadian Mennonite Enlistments During the Second World War”; James Enns, “From Heartland of the Reformation to Post-Christian Mission Field: North American Conservative Protestants and the Mission to West Germany, 1945-74.”